Complejo ecoturístico en Antonio Ante, Atuntaqui - Enderica Velastegui, Dayana Jazmín (2024)
The canton of Antonio Ante has natural, cultural, archaeological, etc. attractions. An ideal scenario for the practice of alternative tourism such as nature tourism. However, by highlighting only its tourist attraction linked to the textile, handicraft and commercial activity, Atuntaqui has become a transitory city where domestic and foreign tourists come for short periods of time, only for commercial purposes. Under this premise, the objective of this work is to diversify the tourist proposal through an urban-architectural intervention that enhances the landscape attractions, promotes ecotourism, generates territorial identity and growth of activities complementary to tourism. In defining the thematic approach, a mixed method combining qualitative and quantitative approaches was chosen, where it was possible to identify important data for the development of the project. Among them, the insufficiency of important services for the development of tourism, such as lodging, food and recreational spaces. After an analysis of the territory considering the existing problems and user needs, three scales of intervention are proposed: the macro scale corresponds to the design of a tourist route that highlights natural, cultural, religious and commercial attractions. The meso scale projects a cultural axis that includes the road design reconfiguring the sidewalk and roadway, as well as a proposal of façade prototypes. The micro scale translates into the design of an ecotourism complex that seeks a connection with nature and is aimed at three types of users. It combines common and traditional construction techniques such as tapial and BTC that reduce the ecological footprint and respond to the identity of the place. The project in its three scales of intervention allows promoting and providing the necessary guarantees to classify Atuntaqui and Andrade Marín as a high impact tourist destination. It also promotes alternative tourism practices that promote the revaluation of its natural attractions and cultural charm by offering a diversity of services and activities that encourage people to stay in the city for longer periods of time, thus combating floating tourism.